2009
DOI: 10.1093/aje/kwp263
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in Xenobiotic Metabolic Pathway Genes, Personal Hair Dye Use, and Risk of Non-Hodgkin Lymphoma

Abstract: From 1996 to 2000, the authors conducted a population-based case-control study among Connecticut women to test the hypothesis that genetic variation in xenobiotic metabolic pathway genes modifies the relation between hair dye use and risk of non-Hodgkin lymphoma. No effect modifications were found for women who started using hair dyes in 1980 or afterward. For women who started using hair dye before 1980 as compared with never users, a statistically significantly increased risk of non-Hodgkin lymphoma was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The methods for evaluating genotypes in our study population have been described previously [12,13]. Briefly, DNA was extracted from blood or buccal cell samples using phenol-chloroform extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for evaluating genotypes in our study population have been described previously [12,13]. Briefly, DNA was extracted from blood or buccal cell samples using phenol-chloroform extraction.…”
Section: Methodsmentioning
confidence: 99%
“…These studies both showed that an increased risk of NHL was observed among women who began using hair dye before 1980 (both OR 1.3) [6, 7]. While our study is the first to our knowledge to evaluate hair dye use and NHL risk in relation to DNA repair polymorphisms, two previous studies have reported that genetic variation in xenobiotic metabolic pathway genes and in NAT1 and NAT2 genes modify the risk of NHL with hair dye use and that these associations are also limited to hair dye use before 1980 [13, 21]. One possible explanation for these differences in risk by time period observed in our study may relate to higher levels of mutagenic chemicals in hair dye formulations before 1980, as reformulation of hair dye products beginning in the early 1980s involved the replacement or elimination of some of the dyes that had been reported to produce tumors in NCI bioassays [22].…”
Section: Discussionmentioning
confidence: 84%
“…We have previously shown that variation in xenobiotic metabolic pathway genes modify the association between hair dye use and NHL risk, particularly for women who started use before 1980 and for the follicular lymphoma (FL) subtype [13]. DNA repair mechanisms are important in maintaining genomic stability, and defects in DNA repair pathways may increase chromosomal aberrations induced by hair dye use [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also investigated effect modifications of genetic variation on the relationship between personal hair dye use and risk of NHL (39, 42, 48, 51) Schroeder et al (51) classified NHL by presence of t(14;18) translocation and found a significant risk for hair dye use in t(14;18)-negative translocation NHL (OR=2.1, 95%CI: 1.3,3.4) but not in t(14;18)-positive translocation NHL (OR=1.8, 95%CI: 0.9,3.7). Another study by Chiu et al (48), however, did not find an association by t(14;18) translocation in either men or women.…”
Section: Non-hodgkin Lymphomamentioning
confidence: 99%
“…A population-based case-control study among Connecticut women was conducted to test whether genetic variation in xenobiotic metabolic pathway genes modifies the relationship between hair dye use and risk of NHL (42). No effect modifications were found for women who started using hair dyes in 1980 or after.…”
Section: Non-hodgkin Lymphomamentioning
confidence: 99%